Knowledge, Motivation and Discipline with Nurse Performance Katobu Health Center - Rasniah Sarumi; Albert; Elna Sari (Politeknik Karya Persada Muna, 2022)
Background: Performance is the appearance of the work of personnel both in quantity and quality in an organization. Some nurses have poor performance due to a lack of knowledge, motivation, and discipline of nurses. This study aims to determine the relationship between knowledge, motivation, and work discipline with the performance of nurses at the Katobu Health Center. Methods: This type of research is an analytical survey with a Cross-Sectional Study approach, the population is 45 people, with a total sampling technique, with a sample of 45 people. The analytical method is used in univariate and bivariate (Chi-square) analyses. Results: There is a relationship between knowledge and nurse performance = 0.013 (ρ < 0.05), There is a relationship between motivation and nurse performance = 0.000 (ρ < 0.05), There is no relationship between discipline and nurse performance p-value = 0.096 > 0, 05. Conclusion: there is a relationship of motivation with the performance of nurses and there is no relationship of discipline with the performance of nurses. It is recommended to the Katobu Health Center to evaluate the performance of nurses, increase the knowledge and motivation of nurses and improve nurse discipline. Keywords: Performance, knowledge, motivation, discipline